An Exploration of the Concept of Well-being In Relation to the Care of Older People - Maria Cheshire-Allen (2022)
This research explores the concept of well-being as it applies to family carers of older people and the experiences of those carers in the light of a reworked version of that concept. The study is situated within a broader context of the ‘care crisis’ consisting of an increase in older age care demands alongside a decrease in the resource or care capacity to support demand, resulting in a so-called ‘care deficit’. Notions of ‘well-being’ have become nested within this crisis narrative. During the past five years, particularly in the UK, references to well-being have been explicitly embedded into social care welfare support programmes, and are used to determine and shape how care support services are delivered to carers and those requiring care. However, as well as being ubiquitous, the term is contentious. Its meaning in the care context has yet to be resolved, and in particular, scant critical attention has been paid to the term’s significance in the context of care for older people. This study responds to this knowledge gap by exploring the meaning and implication of well-being in the context of care of older people. This qualitative research study provides a full analysis of relevant theory, policy and empirical research addressing well-being and family carers. The central research question is: What is well-being in the context of family care of older people, and why does it matter? The research question is explored through an extended critical engagement with relevant well-being and care theoretical foundations (Nussbaum, 2011; Tronto, 2013) and through a policy analysis of the Social Services and Well-being Act (Wales) 2014. A novel theoretical framework founded upon a social justice perspective and drawing upon critical care ethics and the capability approach is developed. Through critical engagement with the latent meaning of well-being, I argue that the mainstream conception in the context of care is narrow and reductive. Based upon and reflecting ideas about older age and care that mute the value of care as an essential component of all human life and, have the potential in practice to limit and damage family carers’ lives and life chances. In the latter part of the thesis, this framework is applied to primary data gathered through thirty qualitative semi-structured interviews with family carers of older people in Wales. The analysis explores how ‘well-being’ as an enduring ideal defining what it means to live a ‘good life’ interacts with how care in older age is understood. The analysis identifies the key themes of well-being as a multidimensional and relational idea, freedom, choice, vulnerability and dependency. From these findings, I suggest that there is value in theorising an imperfect conception of well-being that acknowledges decline and dependence, particularly in older age care. Furthermore, I suggest a reformulation of well-being in the context of older age care, based upon acknowledging relationality, inequalities and socio-political and cultural contexts. Such a conception, I argue, has the potential to provide a firmer basis on which to articulate and tackle well-being within social care policy and to combat harmful assumptions about the place of care of older people within those systems and the value of caring relationships themselves.